2012
DOI: 10.1111/j.1537-2995.2012.03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8 transfusion transmission in Ghana, an endemic region of West Africa

Abstract: BACKGROUND: Human herpesvirus 8 (HHV‐8) seroprevalence ranges between less than 5% in Europe and North America and 50% to 70% in sub‐Saharan Africa. Evidence of HHV‐8 transfusion transmission is only indirect. We conducted a serologic (anti‐HHV‐8) and molecular (HHV‐8 DNA) study of samples from paired donor‐immunocompetent recipients transfused with whole blood. STUDY DESIGN AND METHODS: Samples from 252 donor‐recipient pairs were tested. Immunoglobulin G to HHV‐8 was detected with enzyme immunoassays and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Emerging or known but untested infectious agents were explored to determine the prevalence and potential feasibility and efficacy of screening. This was the case for GB virus‐C, West Nile virus, parvovirus B19, and human herpesvirus 8 24‐27. Syphilis was not tested for until a study was conducted and showed one case of likely transmission .…”
Section: Resultsmentioning
confidence: 99%
“…Emerging or known but untested infectious agents were explored to determine the prevalence and potential feasibility and efficacy of screening. This was the case for GB virus‐C, West Nile virus, parvovirus B19, and human herpesvirus 8 24‐27. Syphilis was not tested for until a study was conducted and showed one case of likely transmission .…”
Section: Resultsmentioning
confidence: 99%
“…60 However, a 2012 Ghanaian study documented seroconversion in a previously seronegative patient following transfusion of HHV8 contaminated WB. 61…”
Section: Hepatitis Virusesmentioning
confidence: 99%
“…However, a few other transfusion‐transmitted infectious agents that are presently not screened but are relatively frequent in sub‐Saharan Africa (SSA) could also be monitored to further demonstrate the in vitro–in vivo correlation of efficacy. Bacterial contamination known to range between 3 and 20% in SSA (Adjei et al, ; Hassall et al, ; Opoku‐Okrah et al, ; Makuni et al, ), and HHV‐8, an intracellular virus present in approximately >20% of SSA blood donors, would be suitable targets (Gobbini et al, ; Hladik et al, ). Efficacy regarding serologically screened viruses, such as HIV‐1/2, HBV or HCV, could not be tested considering the very low prevalence of missed infections.…”
Section: In Vivo Inactivation Of Plasmodium Falciparummentioning
confidence: 99%